Determination of the emission rate for ultrafine and accumulation mode particles as a function of time during the pan-frying of fish. (15th April 2019) - Cho, Hyunwook; Youn, Jong-Sang; Oh, Inhwan; Jung, Yong-Won; Jeon, Ki-Joon
Abstract: Particulate matter (PM) from cooking is considered one of the most harmful indoor air pollutants causing numerous adverse health effects, and it is essential to comprehend the characteristics of the particles generated from cooking to prevent these problems. In this study, we investigated PM from the pan-frying of salmon using number concentration and developed emission rates as a function of time for ultrafine particles (UFPs < 100 nm) and accumulation mode particles (AMPs 0.1–1 μm). The newly defined emission rates vary significantly with time and are very different from the conventionally determined rates that do not consider the variation of particle concentration with time. The emission rate of UFPs decreased over time after a sharp rise, whereas that of AMPs continued to increase, resulting in a change in the proportions of UFPs and AMPs in the total PM from 93 to 7% to 72 and 28%, respectively. Particle–particle interactions such as coagulation and coalescence were observed between primary particles via high resolution transmission electron microscopy (HR-TEM), which is a plausible reason for the decreasing emission rate of UFPs with time. The emission rate as a function of time can serve as a tool to estimate PM from cooking, as well as to monitor the change trends through phenomena such as agglomeration. Highlights: Development of biomass burning emission rate equation as a function of time for UFPs and AMPs Fluctuation of UFPs and AMPs proportions in total PM Observation of particle -particle interaction via TEM analysis